1993
DOI: 10.1128/jvi.67.7.4358-4364.1993
|View full text |Cite
|
Sign up to set email alerts
|

The hypervariable C-terminal tail of the Sendai paramyxovirus nucleocapsid protein is required for template function but not for RNA encapsidation

Abstract: The paramyxovirus nucleocapsid proteins (NPs) are relatively well conserved, except for the C-terminal 20%o (or ca. 100 amino acids), referred to as the tail. We have examined whether this hypervariable tail is required for genome synthesis, both in vitro, where synthesis is predominantly from the input templates, and in vivo, where multiple rounds of amplification occur. In these viruses, genome synthesis and assembly of the nascent chain are coupled. We find that the tail is required in vivo but not in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…In a separate study, all of the NP protein deletion mutants described here have been analyzed for the ability to support replication of Sendai virus defective interfering virion genomes in vitro. Consistent with our results, all NP protein mutants that allowed formation of nucleocapsidlike particles allowed replication in vitro (2). Thus, domain I (positions 1 to 399) also contains all regions required for specific encapsidation of viral genomic RNA.…”
Section: Discussionsupporting
confidence: 90%
“…In a separate study, all of the NP protein deletion mutants described here have been analyzed for the ability to support replication of Sendai virus defective interfering virion genomes in vitro. Consistent with our results, all NP protein mutants that allowed formation of nucleocapsidlike particles allowed replication in vitro (2). Thus, domain I (positions 1 to 399) also contains all regions required for specific encapsidation of viral genomic RNA.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the plasmid-supplied N, P, and L proteins appear to be fully sufficient to support RNA replication, a finding which has also been made with two rhabdoviruses, vesicular stomatitis virus and rabies virus (9,31,37), and the paramyxovirus Sendai virus (2,13). RSV is sufficiently dissimilar that this confirmation is useful.…”
Section: Discussionmentioning
confidence: 65%
“…Rescue means that the minigenome participates in one or more of the major features of the intracellular viral replicative cycle, including RNA replication, transcription, and production of transmissible particles. Studies to date have employed minigenomes such as a cDNAencoded copy of naturally occurring defective interfering RNA (2,13,31,40) and an engineered version of genome RNA containing a large internal deletion and the insertion of a marker gene, usually that for bacterial chloramphenicol acetyltransferase (CAT), under the control of putative transcription signals (6-9, 14, 15, 19, 24-26, 29, 30).…”
mentioning
confidence: 99%
“…Failure to recover infectious virus from the construct with extensive deletion of 48 residues in NDV-⌬48 might be due to the loss of important functional domains in addition to structural constraints. Indeed, the carboxy-terminal region of the NP of Sendai paramyxovirus was shown to be required for template function (8). Whether the corresponding region of the NP of NDV possesses similar function remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NP regulates transcription and replication of the viral genome by interacting with P alone, with P and L, or with itself (NP-NP interaction). For Sendai paramyxovirus, it was shown that a conserved N-terminal region of NP was involved in NP-RNA and NP-NP interaction (5), whereas the carboxyterminal domain was shown to be required for template function (8). Most of the NP is thus absolutely essential for virus replication due to multifold engagement of NP in the assembly and biologic activity of the RNP.…”
mentioning
confidence: 99%